Locus of Control, Whistleblowing, Kesesuaian Kompensasi dan Kecenderungan Kecurangan Akuntansi - Ulantari, Putu Peni; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 33 No 7 (2023), 2023)
The study aims to analyze the effect of locus of control, whistleblowing, and suitability of compensation on the tendency of village credit institutions (LPD) to commit fraudulent accounting. The theory used is the Fraud Triangle Theory. The research was conducted at LPD in Buleleng Regency. The final sample size is 70 LPD officers using purposive sampling method. Data were analyzed using multiple linear regression with the help of SPSS Statistics 25 software. The results showed that locus of control had a positive effect on the tendency of LPD prajuru accounting fraud. Meanwhile, whistleblowing and suitability of compensation have a negative effect on the tendency of LPD employee accounting fraud. Keywords : Locus of Control ; Whistleblowing; Suitability of Compensation; Accounting Fraud Tendency; Village Credit Institution.